Chinese Language Translation of the Sipanjimas Application Registration Guidebook for the Banyumas Licensing Service Information System (DPMPTS Banyumas) - Herliana, Monika; Prasetyowati, Henggar; Aryovather, Puspita Reisy; Haili, Zhuang (International Journal of Chinese Interdisciplinary Studies, 2024)
This article, entitled "Translation of the SIPANJIMAS Application Registration Guidebook (Banyumas Licensing Service Information System) into Chinese at DPMPTSP Banyumas," examines the translation process undertaken during the work practice at DPMPTSP Banyumas from October 10, 2021, to March 13, 2022. The primary objective of this work practice was to develop a Chinese-language version of the SIPANJIMAS application guidebook, facilitating easier online registration for investment, particularly for Chinese-speaking foreigners in Banyumas Regency. This initiative was prompted by the increasing number of foreign investors, especially Chinese speakers, in the region. The research employed a combination of observation, interviews, and internet browsing as data collection methods. The translation of the guidebook utilized the communicative translation method, which involves adapting sentence structures to align with the grammatical conventions of the target language (Mandarin). This approach ensures that Chinese-speaking readers can easily comprehend the guidebook’s content. The outcome of this work practice is the Chinese-language SIPANJIMAS guidebook, which has been submitted to and is now utilized by DPMPTSP Banyumas.